PERSEPSI SISWA TERHADAP KEBIJAKAN TATA TERTIB SEKOLAH DALAM MENANGANI KASUS PELANGGARAN DI MA NURUL KAROMAH GALIS BANGKALAN - Devina Serliyani; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore students' perceptions of school discipline policies in addressing violations at MA Nurul Karomah Galis Bangkalan. Adolescents often experience behavioral turbulence during their transitional phase, requiring guidance through structured school rules. Using a qualitative descriptive method, data were obtained through interviews, observation, and document analysis. The findings indicate that while most students understand the intent behind the rules, their perception of fairness and consistency in implementation varies. Students tend to accept the rules more when they perceive the enforcement as just and educators as role models. Disciplinary policies are effective when paired with consistent communication and a supportive environment.